Offene Reposition und Schrauben‑/Plattenosteosynthese von Mittelhandfrakturen - Spies, Christian; Langer, Martin; Hohendorff, Bernd; Müller, Lars Peter; Oppermann, Johannes; Unglaub, Frank (Operative Orthopädie und Traumatologie, 2019)
ObjectiveAnatomic reduction and stabile fixation for immediate mobilisation and restoration of unrestricted function.IndicationsInstabile metacarpal fractures with or without malrotation, dislocated metacarpal fractures with malrotation or finger extension deficit, longitudinally shortened metacarpal fractures with finger extension deficit.ContraindicationsPersistent infections (empyema, osteomyelitis, phlegmon)Surgical techniqueLongitudinal intermetacarpal incision along the fracture zone, debridement of the fracture zone with retainment of periost, anatomic reduction and retention of spiral fractures with at least two lag screws or retention of comminuted or transverse fractures with locking plate osteosynthesis while retaining periost.Postoperative managementBuddy splinting of the corresponding finger to enable immediate mobilisation without weight bearing for 6 weeks.ResultsLocking plate osteosynthesis and compression screw osteosynthesis after anatomic reduction of metacarpal fractures proved to be very reliable with a low complication rate and a good functional outcome (modified Mayo Wrist Score [MMWS]: mean 88 (20-100); Disabilities of Arm, Shoulder, and Hand (DASH) questionnaire: mean 41(24-86)).